Menavigasi Risiko Pembelian Online: Persepsi Konsumen Dalam Lanskap E-Commerce - Oktaga, Andreas Tigor; Setyowati, Widhy (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
E-commerce has changed the way consumers shop with convenience and access to a wide range of products. Qualitative research was conducted to understand how consumers specifically navigate risk, build trust, and deal with post-purchase psychological impacts in the e-commerce landscape. The research revealed that consumers perceive e-commerce as providing convenience and benefits in shopping, including time flexibility and diverse product choices. However, consumers are also aware of risks, such as product, delivery, data security and financial risks. Consumers exercise judgment by relying on product reviews, review ratings, and sales numbers to reduce risk or take risks. They manage risk by choosing familiar brands or stores and take active steps to deal with risks that may arise. The findings from this research provide valuable insights for e-commerce businesses with the aim of improving online transaction practices, minimizing risk uncertainty, and ultimately creating a more positive shopping experience for consumers. By understanding how consumers respond to risk and build trust, e-commerce businesses can better direct their efforts in creating a safer, more convenient and satisfying shopping environment